Toxicidade de corticoides e biocidas em células da córnea: pesquisa translacional reversa e medicina de precisão em oftalmologia e ciências visuais - Roizenblatt, Marina [UNIFESP] (2016)
INTRODUCTION: Human Corneal Epithelial Cells (HCEC) and Statens Seruminstitut Rabbit Cornea (SIRC) reproduce the cornea microenvironment in terms of epithelium and stroma, respectively. These cells are ideal for the study of the pathophysiology of the Acanthamoeba keratitis (AK) in vitro. . As there is no standartized treatment for AK, it is important to develop a study model for this condition. In addition, considerable toxicity has been reported with the use of antimicrobial compounds such as biguanides and diamidines, associated or not to corticosteroids, for the management of AK. OBJECTIVES. To study the in vitro the effect of isolated corticosteroids or associated with Polyhexamethylene Biguanide (PHMB) in a cell model of the corneal epithelium and stroma. MATERIALS AND METHODS. Cells of HCEC or SIRC were seeded into plates in the concentration of 2 x 105/mL and treated with the addition of corticosteroid (dexamethasone 0.1% or prednisolone 1.0%) or PHMB at the concentration of 0.02% or 0.04%, alone or associated with one of the above mentioned corticosteroids. Cell metabolism were quantified by fluorescence with the aid of PrestoBlueTM RESULTS. Metabolism did not differ between HCEC and SIRC after 6 hours and in the recovery period, in which cells were incubated without the chemical compounds 9 (p<0,01). The metabolic rate of recovery increased in the PHMB 0.02% plus pednisolone condition for HCEC and PHMB 0.04% plus dexamethasone for SIRC (p<0,05). Media supplemented with prednisone or dexamethasone showed to be less toxic than PHMB in any concentration, alone or in association to corticosteroids (p<0,01). DISCUSSION. The literature lacks objective data on the ocular toxicity of PHMB and / or corticosteroids in the treatment of CA. It has been demonstrated that the toxicity of PHMB is higher than that of steroids to cells of the epithelium and corneal stroma at an experimental environment, and that the combination of the two medications did not improve the condition. After removal of the drugs from the culture medium, it was observed a cellular metabolism recovery. CONCLUSIONS. This study demonstrates that the addition of corticosteroids does not change considerably the toxicity of PHMB to the corneal cells. Notwithstanding, PHMB 0.02% is preferable in cases of combined therapy for AK.